Optimization of Counseling Guidance in Preventing the Criminal Action of Curanmor by Binmas Unit, Pemalang Police - Hutapea, Alfredo (Advances in Police Science Research Journal, 2024)
Corona virus disease 2019 (Covid-19), which occurs evenly in various places, has various effects. These effects can be felt directly in society, the economy, education, employment, politics, and health. These conditions affect a country’s economic turnover which causes a slowdown or worsens a situation. This condition causes unemployment in Indonesia to increase. From 2019 to 2022, cases of motor vehicle theft dominate other criminal cases at the Pemalang Police. These crimes disturb the community and occur continuously. The respressive efforts carried out by the Pemalang Police wete not effective enough so that preemptive and preventive efforts wew needed by the Pemalang Police Binmas Unit in carrying out counseling by providing counseling to the community.The problem in this study is why counseling by the Pemalang Police Binmas Unit in preventing the crime of theft has not been optimal. The focus if this research is the implementation of counseling guidance in preventing the crime of motor vehicle theft by the Pemalang Police Binmas Unit. This study used a qualitative approach and the type of research used was field research which was taken by interview, observation, and document study. The data soucrces in this study are primary sources by conducting direct interviews with informants and secondary sources studying the results of documentation, reports, and other written sources. The results showed that the implementation of counseling guidance in preventing the crime of motor vehicle theft and the organizational resources of the Pemalang Police Binmas Unit were not optimal in reducing the number of theft crimes. The things that make the implementation of extension guidance not optimal are the lack of member, low community participation, and the lack of ultiluzation of social media by the Pemalang Police Binmas Unit.